2007
DOI: 10.1080/02640410701275219
|View full text |Cite
|
Sign up to set email alerts
|

The second leg home advantage: Evidence from European football cup competitions

Abstract: The home advantage is a widely acknowledged sporting phenomenon, especially in association football. Here, we examine the second leg home advantage, an effect that is discussed in the public domain but which has received very little scientific attention. The second leg home advantage effect occurs when on average teams are more likely to win a two-stage knock-out competition when they play at home in the second leg. That is, both teams have a home advantage but this advantage is significantly greater for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 30 publications
3
85
1
2
Order By: Relevance
“…At the beginning and at the end of academic year we conducted pedagogic testing for determination of physical and technical fitness. As tests we used standard tests for physical and technical fitness [16,17,19,23,25,27,29,30]. For determination of physical fitness we conducted pedagogic testing: forward…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning and at the end of academic year we conducted pedagogic testing for determination of physical and technical fitness. As tests we used standard tests for physical and technical fitness [16,17,19,23,25,27,29,30]. For determination of physical fitness we conducted pedagogic testing: forward…”
Section: Introductionmentioning
confidence: 99%
“…The second-leg HA found in the present study was in accordance to other authors who investigated the second-leg HA in European tournaments. Page and Page 29 , for example, investigated the second-leg HA effect in European Football Cup competitions (N=6084 two-leg knock-out rounds) and reported the probability of winning at the end of two legs for the second-leg home team of 54.98% 29 . In another study, Eugster, Gertheiss, Kaiser 30 found 56% of the probability of winning in favour of the team having the return match at home in the UEFA Champions League.…”
Section: Discussionmentioning
confidence: 99%
“…The visual revision and assessment were performed blinded by two experienced and independent observers. The procedures were in accordance with previous reports 29,30 .…”
Section: Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…In this natural experiment professionals know exactly the tournament's setting, the payo¤s and incentives are very high, and the process of allocating teams is random. Page and Page (2007) analyze the same knock-out setting. The most important di¤erence between this paper and Page and Page (2007) is that we develop an identi…cation strategy capable of distinguishing between the leading-e¤ect and risk-taking.…”
mentioning
confidence: 99%